Luminescence properties and energy transfer studies in thermally stable Bi2O3: Sm3+, Eu3+ phosphor - Pandey P.K.; Dixit P.; Chauhan V.; Pandey P.C. (My University, 2025)
The advent of innovative rare-earth based metal oxide phosphors has prompted increasing interest in the search for highly efficient red emitting phosphors for various optoelectronic devices, lighting and display applications and motivated the research community to develop some promising, state-of-the-art, and potential red phosphors to meet the necessary requirements. In this study, a series of Sm3+ (1–7 mol%) doped, Sm3+ (5%) doped and Eu3+ (2–5 mol%) co-doped Bi2O3 red phosphors were synthesized by a facile urea assisted auto-combustion process. The X-ray diffraction (XRD) analysis of the phosphors ascertains the tetragonal crystal structure without any trace of impurity. The UV-Vis-NIR absorption study of the phosphors was carried out in 200–1000 nm range and the estimated optical band gap of the phosphors was lying in the range of 2.778–2.831 eV. The photoluminescence (PL) emission studies were performed at an excitation wavelength of 481 nm in the 550–720 nm range. The effective energy transfer mechanism from Sm3+ to Eu3+ in the Bi2O3 phosphor has been ascribed to the dipole-dipole (d-d) interaction. The energy transfer process was further validated by PL decay time measurements. The CIE color coordinates were obtained using PL emission data. The CIE chromaticity diagram ascertains that the emission color of Bi2O3: Sm3+ phosphors were tuned from reddish-orange to the red region by varying the concentration of Eu3+ ions. The temperature dependent PL study of the phosphors was taken out in the range of 293–453 K and was found thermally stable at elevated temperatures. © 2023 Elsevier B.V.